Kinetic analysis reveals bacterial efficacy for biodegradation of chlorpyrifos and its hydrolyzing metabolite TCP - Maya K.; Singh R.S.; Upadhyay S.N.; Dubey S.K. (My University, 2025)
Efficacy of soil bacterial communities comprising seven different isolates for biodegradation of chlorpyrifos and TCP (3,5,6-trichloro-2-pyridinol), a degradation product of chlorpyrifos, has been investigated. The concentration of chlorpyrifos has ranged from 25 to 200 mg chlorpyrifos/L, and that of TCP from 25 to 100 mg TCP/L. The average values of Ks and Vmax are found to be different for isolates 1-4, 5-6 and 7 for both chlorpyrifos and TCP. The Ks has ranged from 97 to 142.3 mg/L and Vmax from 7.4 to 12.1 mg/L/d for chlorpyrifos and 103.09 to 148.8 mg/L and 14.9 to 21.2 mg/L/d, respectively, for TCP. Results indicate the high affinity of bacterial community for degradation of both chlorpyrifos and TCP. The 16S rRNA gene sequence analysis has confirmed the genetic relatedness of isolates 1-4 with Pseudomonas, isolates 5 and 6 with Agrobacterium, and isolate 7 with Bacillus. Their degradation potential for chlorpyrifos and TCP has been found to be in the order: Pseudomonas > Agrobacterium > Bacillus. It has been also observed that all seven isolates are more efficient in degrading TCP compared to chlorpyrifos. © 2011 Elsevier Ltd. All rights reserved.